2022
DOI: 10.4111/icu.20220179
|View full text |Cite
|
Sign up to set email alerts
|

Role of oral pentosan polysulfate in Bacillus Calmette–Guérin therapy in patients with non-muscle-invasive bladder cancer

Abstract: Purpose Intravesical Bacillus Calmette–Guérin (BCG) instillation, although an important treatment for non-muscle-invasive bladder cancer, exerts local and systemic adverse effects. Pentosan polysulfate (PPS) is a bladder mucosal protective drug that acts by replacing mucus in the glycosaminoglycan layer of the damaged urothelium. We hypothesized that co-administration of oral PPS with BCG instillation would relieve BCG-related adverse effects without affecting its efficacy. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Treatments that have been used successfully to treat IC/BPS symptoms, including pentosane polysulfate (PPS), via restoration of urothelial permeability have been proposed as promising treatments for preventing BCG induced LUTS. In a clinical cohort of 217 patients receiving BCG instillations for NMIBC, co-administration of oral PPS thrice daily effectively decreased the BCG discontinuation rate compared to placebo (15.6% vs. 6.3%) without impacting BCG efficacy (Lee et al, 2022 ). A separate small study showed oral PPS was effective in reducing BCG induced LUTS with a reduction in the post-treatment Visual Analog Scale (VAS) score for pain, the post-treatment OAB-V8 score, and dysuria (Yadav et al, 2016 ).…”
Section: Clinical Management Strategies For Bcg Induced Lutsmentioning
confidence: 99%
“…Treatments that have been used successfully to treat IC/BPS symptoms, including pentosane polysulfate (PPS), via restoration of urothelial permeability have been proposed as promising treatments for preventing BCG induced LUTS. In a clinical cohort of 217 patients receiving BCG instillations for NMIBC, co-administration of oral PPS thrice daily effectively decreased the BCG discontinuation rate compared to placebo (15.6% vs. 6.3%) without impacting BCG efficacy (Lee et al, 2022 ). A separate small study showed oral PPS was effective in reducing BCG induced LUTS with a reduction in the post-treatment Visual Analog Scale (VAS) score for pain, the post-treatment OAB-V8 score, and dysuria (Yadav et al, 2016 ).…”
Section: Clinical Management Strategies For Bcg Induced Lutsmentioning
confidence: 99%